1981
DOI: 10.1073/pnas.78.6.3591
|View full text |Cite
|
Sign up to set email alerts
|

Glucose induces two amino acid transport systems in Chlorella.

Abstract: In autotrophically grown ChloreUa.cells, glucose induces a hexose transport system but, at the same time, the synthesis of two amino acid transport systems is also induced. Thus, the rates of uptake of glycine, L-alanine, L-proline, and L-serine, all of which compete with each other for entry into the cells, increase more than 1004fold when the algae are pretreated with glucose. The rates of L-arginine and L-lysine uptake increase by a factor of 25 to 50. The accumulation of proline and arginine within the cel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0
1

Year Published

1984
1984
2018
2018

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 51 publications
(24 citation statements)
references
References 14 publications
0
23
0
1
Order By: Relevance
“…In contrast, Chlamydomonas reinhardtii 6145c cells can deaminate twelve L-amino acids by means of a deaminase activity which required acetate for induction and never occurred in nitrogen-free cultures. In this connection, the ratio carbon/ nitrogen has been proposed as responsible for the induction of an amino acid permease in Chlorella (Cho et al 1981), and a" superderepression" of asparaginase activity has been found in Saccharomyees cerevisiae cells incubated with glucose (Pauling and Jones 1980). Deaminase activity induction depended on de-novo protein synthesis, since cychloheximide prevented cells from deaminating amino acids (Fig.…”
Section: Resultsmentioning
confidence: 96%
See 1 more Smart Citation
“…In contrast, Chlamydomonas reinhardtii 6145c cells can deaminate twelve L-amino acids by means of a deaminase activity which required acetate for induction and never occurred in nitrogen-free cultures. In this connection, the ratio carbon/ nitrogen has been proposed as responsible for the induction of an amino acid permease in Chlorella (Cho et al 1981), and a" superderepression" of asparaginase activity has been found in Saccharomyees cerevisiae cells incubated with glucose (Pauling and Jones 1980). Deaminase activity induction depended on de-novo protein synthesis, since cychloheximide prevented cells from deaminating amino acids (Fig.…”
Section: Resultsmentioning
confidence: 96%
“…This takes place either by means of energy-dependent transport systems (Kirk and Kirk 1978a, b;Cho et al 1981;Cho and Komor 1983;Flynn and Syrett 1985;Sauer and Tanner 1985) or by deamination mechanisms occurring at the cell surface with the subsequent uptake and assimilation of the ammonium produced Cooksey 1979, 1981a, b).…”
Section: Introductionmentioning
confidence: 99%
“…It is possible that the regulatory signal may not be an N compound at all, but a compound derived from, for example, carbon metabolism. Indeed, both glucose and non-metabolizable glucose analogues have been reported to induce amino acid transporters in algae, illustrating the tight interdependence of carbon and nitrogen metabolism (Cho et al 1981). The ability to up-regulate amino acid uptake in response to N deficiency suggests that amino acid uptake plays a significant role in the N scavenging of the plant.…”
Section: Discussionmentioning
confidence: 99%
“…The simplest explanation is that glucose acts directly on intestinal cells, inducing synthesis of transport protein. Transported but nonmetabolized glucose analogues fail to mimic glucose's ability to restore monosaccharide transport in fasted rats (Roy & Dubois, 1972;Debnam & Levin, 1976), but do induce glucose transport in the alga Chlorella (Cho, Sauer, Komor & Tanner, 1981).…”
Section: Discussionmentioning
confidence: 99%